Rationale for the Use of Upfront Whole Brain Irradiation in Patients with Brain Metastases from Breast Cancer - Tallet, Agnes V. (Molecular Diversity Preservation International (MDPI), 2014)
Breast cancer is the second most common cause of brain metastases and deserves particular attention in relation to current prolonged survival of patients with metastatic disease. Advances in both systemic therapies and brain local treatments (surgery and stereotactic radiosurgery) have led to a reappraisal of brain metastases management. With respect to this, the literature review presented here was conducted in an attempt to collect medical evidence-based data on the use of whole-brain radiotherapy for the treatment of brain metastases from breast cancer. In addition, this study discusses here the potential differences in outcomes between patients with brain metastases from breast cancer and those with brain metastases from other primary malignancies and the potential implications within a treatment strategy.